Electrode Potential Dependency of Single-Cell Activity Identifies the Energetics of Slow Microbial Electron Uptake Process - Deng, Xiao; Okamoto, Akihiro (Frontiers in Microbiology, 2018)
Electrochemical measurements have been widely applied to study microbial extracellular electron transport processes. However, because electrochemistry detects not only microbial electron transport but also other background reactions, background signals comparable to or larger than microbial ones hamper the identification of microbial electron transport energetics. This problem is crucial especially for the detection of electron uptake processes by slow-growing microbes in low-energy subsurface sediments, as the environmental samples contain electrochemically active humus and mineral particles. In this study, we report a cell-specific stable isotope analysis to quantify the electrode potential dependency of anabolic activity in individual cells for identifying the electron uptake energetics of slow-growing bacteria. Followed by the incubation of Desulfovibrio ferrophilus IS5 cells with isotopic 15N-ammonium as the sole N source on electrodes poised at potentials of –0.2, –0.3, –0.4 and –0.5 V [versus standard hydrogen electrode (SHE)], we conducted nanoscale secondary ion mass spectroscopy (NanoSIMS) to quantify 15N assimilation in more than 100 individual cells on the electrodes. We observed significant 15N assimilation at potentials of –0.4 and more 15N assimilation at –0.5 V, which is consistent with previous reports in IS5 cells of the onset potential for electron uptake via outer-membrane cytochromes (OMCs). The activation of cell energy metabolism was further examined by transcriptome analysis. Our results showed a novel methodology to study microbial electron uptake energetics. The results also serve as the first direct evidence that energy acquisition is coupled to the electron uptake process in ubiquitous sulfate-reducing bacteria, with implications on the electron-fueled subsurface biosphere hypothesis and other microbial processes, such as anaerobic iron corrosion and anaerobic methane oxidation.